2007
DOI: 10.1529/biophysj.106.100339
|View full text |Cite
|
Sign up to set email alerts
|

Protein Secondary Structure and Orientation in Silk as Revealed by Raman Spectromicroscopy

Abstract: Taking advantage of recent advances in polarized Raman microspectroscopy, and based on a rational decomposition of the amide I band, the conformation and orientation of proteins have been determined for cocoon silks of the silkworms Bombyx mori and Samia cynthia ricini and dragline silks of the spiders Nephila clavipes and Nephila edulis. This study distinguished between band components due to beta-sheets, beta-turns, 3(1)-helices, and unordered structure for the four fibers. For B. mori, the beta-sheet conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
405
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 386 publications
(449 citation statements)
references
References 62 publications
42
405
2
Order By: Relevance
“…Typically, the b-sheet content that is found by this method is 37 6 3% for the dragline, 45 6 3% for the cocoon silk of S. c. ricini and 50 6 3% for that of B. mori, 33 which is basically consistent with crystallinity measurements. 11,[44][45][46][47] Comparison between the b-sheet content determined from the spectroscopic data and the percentage of amino acids that may potentially be included into the b-sheets lead to the conclusion that for the dragline fiber the AG and GGA motifs adjacent to the (A) n are incorporated into the b-sheets, 33 which is consistent with the literature. [48][49][50] Other results have shown that the minor ampullate (Mi) and cylindriform (Cyl) silks belong to the same structural family than the Ma silk as they are composed of highly oriented b-sheets (35-37%) dispersed in an amorphous matrix made of other slightly oriented secondary structures.…”
Section: Determination Of the Protein Secondary Structuresupporting
confidence: 76%
See 3 more Smart Citations
“…Typically, the b-sheet content that is found by this method is 37 6 3% for the dragline, 45 6 3% for the cocoon silk of S. c. ricini and 50 6 3% for that of B. mori, 33 which is basically consistent with crystallinity measurements. 11,[44][45][46][47] Comparison between the b-sheet content determined from the spectroscopic data and the percentage of amino acids that may potentially be included into the b-sheets lead to the conclusion that for the dragline fiber the AG and GGA motifs adjacent to the (A) n are incorporated into the b-sheets, 33 which is consistent with the literature. [48][49][50] Other results have shown that the minor ampullate (Mi) and cylindriform (Cyl) silks belong to the same structural family than the Ma silk as they are composed of highly oriented b-sheets (35-37%) dispersed in an amorphous matrix made of other slightly oriented secondary structures.…”
Section: Determination Of the Protein Secondary Structuresupporting
confidence: 76%
“…33 On the basis of these assumptions, the orientation distribution function, N(h), which represents the probability of finding a given structural unit oriented at an angle h with respect to the fiber axis, can be expanded into a series of Legendre polynomials P ' (cos h) such as 31 :…”
Section: Quantitative Determination Of the Molecular Orientationmentioning
confidence: 99%
See 2 more Smart Citations
“…1a) [6][7][8]. Thereby, the anti-parallel beta-sheet nanocrystals [9][10][11][12] play a key role in defining the mechanical properties as they provide stiff orderly cross-linking domains embedded in a semiamorphous matrix that consists of less orderly beta-structures, 3 1 helices and beta-turns [6,13,14].…”
Section: Introductionmentioning
confidence: 99%